Distributed Collaborative Control Strategy for Intra-regional AGC Units in Interconnected Power System with Renewable Energy - Lei ZHANG; Xiaowei MA; Manliang WANG; Li CHEN; Bingtuan GAO (Zhongguo dianli)
In the regional power grid where a large number of renewable energy stations are equipped with automatic generation control (AGC) functionality, the response characteristics of different frequency regulation units vary significantly, which may aggravate the computation load of the centralized controller and affect the frequency control performance of the regional power system. In response to the above challenges, a collaborative control strategy for intra-regional AGC units in interconnected power system based on unit dynamic model and distributed consistency is proposed, while power interchange is dispatched across different regional power systems according to tie-line power flow and the bias of frequency. Firstly, the frequency response models for different types of frequency regulation units are established. Then, considering the frequency regulation economy, a power dynamic allocation optimization model is constructed, with the objective of minimizing the quadratic cost function of active power variation constrained by active power output and power balance. It is also proved that the objective of economic optimization for frequency regulation can be fulfilled by setting reasonable coefficients, without directly solving the optimization problem. Hence, an AGC frequency control strategy based on distributed consistency algorithm is proposed to determine the settings of intra-regional AGC commands. Finally, taking a three-area interconnected power system as an example, the results show that the proposed strategy can effectively improve frequency regulation performance and reduce the frequency regulation cost.